Breast neuroendocrine tumors multidisciplinary treatment. Single experience in our Centre - Lucia Stella Curto; Rita Gervasi; Nadia Innaro (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Introduction: Breast Neuroendocrine Tumours (B-NETs) are rare entities; the incidence in Italy is about 1%. The great variability of manifestations and localizations made it very interested in studying. Only few cases are available in literature; actually this pathology is more difficult to treat because specific guidelines don't exist for the treatment of primary metastatic NETs. Case presentation: The case concerns a 48-year-old woman with a diagnosis of Breast Neuroendocrine Tumours (B-NET). She was treated with multidisciplinary approach; the patient started neoadjuvant chemotherapy and then she underwent right radical mastectomy. No further chemotherapy treatment was performed. In the last ten years, no signs of local recurrence or metastases were observed. Conclusion: The presented case is very characteristic for its multidisciplinary approach.